Analisis Kebutuhan Media Pembelajaran Berbasis Petualangan pada Materi Teks Cerita Kelas IV SDN Gedongombo V - Fifi Yulia Siswanti; Novialita Angga Wiratama; Wendri Wiratsiwi (Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the need for learning media for fourth-grade elementary school students' narrative texts. This study used a descriptive qualitative approach involving one class teacher and 31 fourth-grade students at SDN Gedongombo V. Data collection techniques used included observation, interviews, and documentation. Data were analyzed using an interactive model developed by Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results showed that learning tended to be dominated by lectures and assignments with media limited to textbooks and whiteboards. This condition resulted in students easily getting bored, being less involved in the learning process, and facing difficulties in understanding and writing narrative text messages coherently. Students also showed a higher interest in digital media-based learning and game activities. These findings indicate the need to develop adventure-based learning media that are able to integrate interactive elements, games, and story-based activities to support students' message writing skills more meaningfully.